Dynamics of native oxide growth on CdTe and CdZnTe X-ray and gamma-ray detectors. Issue 1 (1st December 2016) - Zázvorka, Jakub; Franc, Jan; Beran, Lukáš; Moravec, Pavel; Pekárek, Jakub; Veis, Martin
Abstract: We studied the growth of the surface oxide layer on four different CdTe and CdZnTe X-ray and gamma-ray detector-grade samples using spectroscopic ellipsometry. We observed gradual oxidization of CdTe and CdZnTe after chemical etching in bromine solutions. From X-ray photoelectron spectroscopy measurements, we found that the oxide consists only of oxygen bound to tellurium. We applied a refined theoretical model of the surface layer to evaluate the spectroscopic ellipsometry measurements. In this way we studied the dynamics and growth rate of the oxide layer within a month after chemical etching of the samples. We observed two phases in the evolution of the oxide layer on all studied samples. A rapid growth was visible within five days after the chemical treatment followed by semi-saturation and a decrease in the growth rate after the first week. After one month all the samples showed an oxide layer about 3 nm thick. The oxide thickness was correlated with leakage current degradation with time after surface preparation. Abstract :